2009
DOI: 10.1158/1535-7163.mct-08-0854
|View full text |Cite
|
Sign up to set email alerts
|

Effective sensitization of temozolomide by ABT-888 is lost with development of temozolomide resistance in glioblastoma xenograft lines

Abstract: Resistance to temozolomide and radiotherapy is a major problem for patients with glioblastoma but may be overcome using the poly(ADP-ribose) polymerase inhibitor ABT-888. Using two primary glioblastoma xenografts, the efficacy of ABT-888 combined with radiotherapy and/or temozolomide was evaluated. Treatment with ABT-888 combined with temozolomide resulted in significant survival prolongation (GBM12: 55.1%, P = 0.005; GBM22: 54.4%, P = 0.043). ABT-888 had no effect with radiotherapy alone but significantly enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 25 publications
4
78
1
Order By: Relevance
“…MGMT, being a suicide enzyme depleted on activation, was minimally decreased in all xenografts after treatment, indicating that MGMT is active in MGMT + lines, although not sufficient to render resistance to therapy. These results are in contrast to recent studies on primary human glioma xenografts where MGMT + lines exhibited resistance to ABT-888+TMZ combination therapy (38). The underlying reasons for differential sensitivity to ABT-888+TMZ in MGMT + lines are not clear but may reflect tumor type-dependent responses.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…MGMT, being a suicide enzyme depleted on activation, was minimally decreased in all xenografts after treatment, indicating that MGMT is active in MGMT + lines, although not sufficient to render resistance to therapy. These results are in contrast to recent studies on primary human glioma xenografts where MGMT + lines exhibited resistance to ABT-888+TMZ combination therapy (38). The underlying reasons for differential sensitivity to ABT-888+TMZ in MGMT + lines are not clear but may reflect tumor type-dependent responses.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the enhancement of TMZ activity by ABT-888+TMZ was not surprising in TMZ-sensitive models. Interestingly, ABT-888+TMZ was significantly efficacious in most of the models examined, including those that were initially resistant or became resistant to TMZ, indicating that PARP inhibition can confer sensitivity to TMZ-refractory tumors perhaps through BER-mediated repair mechanisms (16,17,38). Therefore, TMZ response was not an absolute predictor of enhanced sensitivity to ABT-888+TMZ combination therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Despite being an attractive therapeutic target, PARP inhibitors have achieved mixed results in biologic and clinical studies (28,30,31,47). We demonstrated that while all the PARP inhibitors tested effectively inhibited PARP activity, not all were able to reduce pHGA and DIPG tumor cell growth.…”
Section: Discussionmentioning
confidence: 86%
“…This led us to hypothesize that PARP inhibition could potentially be used as a monotherapy or to enhance the therapeutic index of ionizing radiation (IR) in pHGA and DIPG. Veliparib, olaparib, and niraparib are three orally available PARP inhibitors which have all entered phase III clinical trials for adult cancer, demonstrating good tolerability in phase II studies (25)(26)(27)(28)(29)(30)(31). However, there is a lack of knowledge regarding the efficacy of these PARP inhibitors in pediatric brain tumors.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cancer-type specific responses cannot be ruled out as it has been suggested that only MGMT À leukemia and glioblastoma multiforme cells would respond to temozolomide combined with the PARPi veliparib (40,43,44). It is nevertheless important to consider that variables such as differences in PARPi action, bioavailability, or the application of particular treatment regimes need to be taken into account to correlate in vitro and in vivo efficacy of temozolomide and PARPi combinations as well as clinical efficacy (31,(42)(43)(44)(45). Indeed, to synergize with temozolomide, both drugs work through catalytic PARP inhibition and trapping PARP-DNA complexes.…”
Section: /Mgmtmentioning
confidence: 99%